The Review Reviewed: Stop Publication Bias - de Ru, Jacob Alexander; de Groot, John C. M. J.; Elshof, Jan-Willem M. (Journal of Scientific Exploration, 2012)
This manuscript describes our past experiences with reviewers and the review procedures that are currently used in the medical sciences. We conclude that reviewers all too often are biased, whereas scientific discussion should be based on substantive comments and without prejudice. In our opinion, subjective arguments for rejection of manuscripts constitute a serious threat to evidence-based medicine. Since peer review should aim to facilitate the introduction into medicine of improved ways of curing, relieving, and comforting patients, a more objective review system with greater scope for the publication of divergent opinions is clearly needed to ensure that a literature search does not merely produce a plethora of articles with mainstream opinions. Our recommendations for a peer review system are: (1) No more anonymous reviewers; (2) The reviewer must concentrate initially on two questions: (a) was a real problem formulated in this manuscript? and (b) is the conclusion—if proven—relevant for practical situations? Keywords: publication bias—evidence-based medicine—review